Advisory Opinion OC-28/21 on Presidential Re-election without Term Limits (Inter-Am. Ct. H.R.). (October 2022) - Cerna, Christina M.
Abstract : In 1959, the Fifth Meeting of Consultation of Ministers of Foreign Affairs of the Organization of American States (OAS) took place in Santiago, Chile. At that meeting, the Inter-American Commission on Human Rights was created by a political resolution rather than by a treaty, as in Europe. Closely related to the question of promoting human rights was the issue of promoting democracy. Article 3(d) of the OAS Charter proclaims that, "[T]he solidarity of the American States and the high aims which are sought through it require the political organization of those States on the basis of the effective exercise of representative democracy, " yet the Charter made no attempt to define democracy. In order to fill this gap, the 1959 Declaration of Santiago, also adopted at this meeting, attempted to identify "some of the principles and attributes of the democratic system in this hemisphere" and the one that interests us here is: "Perpetuation in power, or the exercise of power without a fixed term and with the manifest intent of perpetuation, is incompatible with the effective exercise of democracy."